HIGHWALL SLOPE STABILITY ANALYSIS USING LIMIT EQUILIBRIUM METHOD IN PIT A PT XYZ - Alif Zahrandika, Muhammad
PT XYZ is one of the coal mining companies in East Kalimantan Province which is conducting mining operations in Pit A. In this final project research, the stability analysis of PT XYZ's Pit A highwall slopes was carried out using the limit equilibrium method. Analysis of the stability of the highwall slope was carried out by considering the vibration factor due to blasting of 0.03g and 0.05g and the condition of the groundwater table with hu = 1, hu = 0.8, and hu = 0.6. Referring to the provisions of the Minister of Energy and Mineral Resources Decree No. 1827/K/30/MEM/2018, the minimum permissible dynamic factor of safety (FK) value is 1.1. From the analysis of the existing highwall slope model, it was found that the FK value was still less than 1.1 for conditions hu = 1 and hu = 0.8 which indicated that the slope was in an unsafe condition. Furthermore, a recommendation is given to resloping the highwall slope with the amount of slope adjusting for each existing condition until a dynamic safety factor of more than 1.1 is obtained.